A Strategy Using Pluripotent Stem Cell-Derived Hepatocytes for Stem Cell-Based Therapies - Tomotsune, Daihachiro; Sato, Fumi; Yoshie, Susumu; Shirasawa, Sakiko; Yokoyama, Tadayuki; Kanoh, Yoshiya; Ichikawa, Hinako; Mogi, Akimi; Yue, Fengming; Sasaki, Katsunori (IntechOpen, 2011)
None